Advancing decision support for climate adaptation in agriculture and natural resources - Ikendi, Samuel; Lyons, Andrew; Pathak, Tapan B. (Frontiers in Environmental Science, 2025)
Climatic changes in California require farmers to develop adaptation strategies to sustain their production. Decision support is a key element of climate adaptation but requires a robust understanding of producer needs and priorities. One approach to sharing adaptation information and gathering stakeholder interests and needs is through workshops. This investigation was conducted among 78 technical service providers in a session on adaptation decision support during the 2023 California Adaptation Forum. We adopted a constructivist orientation to understand stakeholder interests and needs on decision support during a 30-minutes dialogue. Four questions were discussed, and participants recorded their responses on different colored sticky notes which were analyzed thematically. Five interrelated themes were uncovered relating to the lived experiences of service providers in making decisions including climate impacts, community engagement and equity, adaptation programs, resources, and cost-benefit analysis. In making those decisions, the most used information sources and tools were community and tribal knowledge, reports like climate assessment reports, and specialized data portals such as Cal-Adapt, CalEnviroScreen, and Healthy Places Index. Several interconnected themes emerged around stakeholder perceptions of gaps in existing decision support resources, the relevance of decision support, and what researchers should focus on. These themes underscore the importance of data translation, visualization, and community engagement to harness stakeholder lived experiences, dissemination, and training to improve data access. We conclude there is a need to engage technical service providers in extension programs on adaptation decision support, equip them with necessary tools such as curricula and resources that will help in advising.